Physical Strength Improvement of Nata de Coco by Water Replacement with Carboxymethylcellulose (CMC) as A Potential Bulletproof Material: A Preliminary Study - Bolilanga, Patricya Inggrid Wilhelmina; Sekarini, Artanti; Toharani, Dita Cinta; Rahmawati, Fani; Basuki, Rahmat; Ishartono, Bayu; Fahri, Mirad (Indonesian Journal of Chemical Studies, 2022)
The dependence on the imported bullet-proof vest  as one of the main equipments of the National Defense System needs attention. This condition treats the independence of domestic defense security. In contrast, the potential of natural materials for bullet-proof vest plates are abundant in Indonesia. Nata de Coco is one of the natural raw materials for producing bullet-proof vest plates that has the potential to be developed. This preliminary research proved that increasing the bond strength of cellulose in Nata de Coco was performed by adding the appropriate crosslinkers. The addition of carboxymethylcellulose (CMC) 2% crosslinker to form Nata de Coco kevlar-like plates (Navlar) was evidenced to increase threefold tensile strength (99.15 MPa) from its original Nata de Coco (31.92 MPa). The development of Navlar is a very strategic sector for producing high-quality bullet-proof vest plates equivalent to kevlar strength. Navlar is more prospective than Kevlar due to its abundant source, cheap, lightweight, and ease to manufacture. Developing Navlar could replace the dependence on imported Kevlar and support the domestic defense industry.